miR-195-5p Suppresses the Proliferation, Migration, and Invasion of Oral Squamous Cell Carcinoma by Targeting TRIM14 - Wang, Tong (Biomed Res Int, 2017)
MicroRNAs (miRNAs) play an essential role in tumor biological processes through interacting with specific gene targets. The involvement of miR-195-5p in cell proliferation, invasion, and migration has been demonstrated in several cancer cell lines, while its function in oral squamous cell carcinoma (OSCC) remains unclear. Here we find that miR-195-5p expression is lower in OSCC than in nontumor tissues, while its overexpression in cell lines can lead to the promotion of apoptosis and the reduction of cell growth, migration, and invasion. Moreover, we identify the tripartite motif-containing protein (TRIM14) as a target of miR-195-5p. Therefore, we reason that the tumor suppressor role of miR-195-5p in OSCC is dependent on the interaction with TRIM14.